Food, Fire, and Ovens: New Archaeological Discoveries at Al Baleed from the Italian Archaeological Mission (2024 Season) - Giunta, Roberta; Pavan, Alexia; Antonelli, Amanda; Valentini, Rosario (Archeologie tra Oriente e Occidente, 2025)
The excavation activities of the Italian Archaeological Mission of the University of Naples L’Orientale at Al Baleed (IAMOB), carried out during the November-December 2024 campaign, focused on mound BA017. This area, which had never previously been subject to archaeological investigation, is located central-western part of the site, near the citadel and the Great Mosque. For the first time at Al Baleed, the ancient city of Ẓafār, a well-preserved production area dedicated to food preparation and cooking was uncovered. Likely part of a larger complex, the area revealed seven freestanding clay ovens (tannurs), hearths, ash pits, and installations for food processing. Associated finds included bread moulds, incense burners, pottery vessels, and personal ornaments. These artefacts suggest that the area was active between the 17th and 19th centuries, corresponding to the final occupational phases of the town.